Vitamin D3 alleviates inflammation in ulcerative colitis by activating the VDR-NLRP6 signaling pathway - Gao, Hongliang; Zhou, He; Zhang, Zhiqiang; Gao, Jianshu; Li, Jian; Li, Xinxia (Frontiers in Immunology, 2023)
Inflammation is a key factor in the development of ulcerative colitis (UC). 1,25-dihydroxyvitamin D3 (1,25(OH)2D3, VD3), as the major active ingredient of vitamin D and an anti-inflammatory activator, is closely related to the initiation and development of UC, but its regulatory mechanism remains unclear. In this study, we carried out histological and physiological analyses in UC patients and UC mice. RNA sequencing (RNA-seq), assays for transposase-accessible chromatin with high-throughput sequencing (ATAC-seq), chromatin immunoprecipitation (ChIP) assays and protein and mRNA expression were performed to analyze and identify the potential molecular mechanism in UC mice and lipopolysaccharide (LPS)-induced mouse intestinal epithelial cells (MIECs). Moreover, we established nucleotide-binding oligomerization domain (NOD)-like receptor protein nlrp6-/- mice and siRNA-NLRP6 MIECs to further characterize the role of NLRP6 in anti-inflammation of VD3. Our study revealed that VD3 abolished NOD-like receptor protein 6 (NLRP6) inflammasome activation, suppressing NLRP6, apoptosis-associated speck-like protein (ASC) and Caspase-1 levels via the vitamin D receptor (VDR). ChIP and ATAC-seq showed that VDR transcriptionally repressed NLRP6 by binding to vitamin D response elements (VDREs) in the promoter of NLRP6, impairing UC development. Importantly, VD3 had both preventive and therapeutic effects on the UC mouse model via inhibition of NLRP6 inflammasome activation. Our results demonstrated that VD3 substantially represses inflammation and the development of UC in vivo. These findings reveal a new mechanism by which VD3 affects inflammation in UC by regulating the expression of NLRP6 and show the potential clinical use of VD3 in autoimmune syndromes or other NLRP6 inflammasome-driven inflammatory diseases.